Challenges of Translating Lexical, Poetic, and Cultural Elements of Shakespearean Selected Sonnets by Tow Arabic Translators: Tantangan Menerjemahkan Elemen Leksikal, Puitis, dan Budaya dalam Soneta Pilihan Shakespeare oleh Dua Penerjemah Arab - Salem, Abdullah Mohammed; Saleh, Aswan Ali Mansoor (Journal of Literature and Education, 2025)
This study explores the challenges of translating Shakespeare's sonnets into Arabic through a comparative analysis of translations by Badr Tawfiq and Bushra Ayoob. The research investigates the extent to which poetic elements, such as rhyme, rhythm, figurative language, and cultural connotations, can be effectively transferred into Arabic without compromising their aesthetic value. Utilizing a qualitative comparative method, the research focuses on two selected sonnets, analyzing lexical choices, poetic rhythm, and cultural symbolism. The analysis is enhanced by the framework of Ashuja'a and Saeed (2018), which incorporates five distinct translation strategies. Findings reveal that Tawfiq’s translation remains faithful to the original text's structure and content, whereas Ayoob’s version demonstrates greater flexibility and cultural adaptation to suit Arabic poetic traditions. The study concludes that poetry translation transcends literal transfer, representing a creative process that requires a delicate balance between accuracy and artistic innovation. This is particularly crucial when addressing rich literary texts like Shakespeare’s works. This research contributes to the field of literary translation by highlighting the necessity of aesthetic and cultural sensitivity in producing successful poetic renditions.